Disability and adult life: dependence on social security among former students with special educational needs in their late twenties. (21st March 2013) - Myklebust, Jon Olav
Abstract : This article, by Jon Olav Myklebust from Volda University, Norway, presents analyses of social security dependence among students with special educational needs in Norway who at the start of upper secondary school had various disabilities – of a somatic, psychological and/or social nature. They were all educated in ordinary schools, in special or regular classes. These young people have been followed prospectively from their first years in upper secondary school and into their late twenties. The analyses indicate which circumstances contribute to social security dependence, with an emphasis on how the independent variables differently influence social security dependence among men and women.